The effect of depth of embedment on the design of spread footing - Adajar, Mary Ann Q. (Animo Repository, 2002)
Spread footings subjected to large overturning moment require large footing dimensions. It is because the extreme soil pressure at the toe of the footing resulting from such loading condition has to be kept within the allowable bearing value. The present footing design procedure relies merely on the bearing capacity of the underlying soil to resist the applied overturning moment. In the design of retaining structures such as bulkheads, retaining walls and abutments, the effect of earth pressure at certain depth of embedment and the weight of the overlying soil are taken into considerations, but these factors are not considered in the present state-of-the art design of spread footing. This study is carried out to determine the probable reduction in the overturning moment on footings if the effect of depth of embedment, as well as its other interrelated factors, are considered in the design process.In order to investigate the effect of embedment on the design of spread footing, both numerical and experimental studies were carried out. This research consists mainly of a series of laboratory experiments, theoretical investigation, and application of the derived theory from this study in the design of spread footing with the purpose of reducing the required footing dimension. In the laboratory experiments, each scale-model footings of various shapes and sizes and concrete post were subjected to horizontal loadings at different depths of embedment. It was observed that backfill material on the toe side of the column and the overlying soil on the heel side of footing were greatly affected by the applied overturning moment. The post stability depends on the passive action of the overlying soil on its side. Footing without overburden soil resists the applied loads because of the resistance offered by the column weight and footing. Theoretical investigation was done by determining the resistance of the scaled-model footing and post to overturning or rotation. The result shows that the passive earth pressure on the side of the column/footing, the weight of the column/footing and the weight of the overlying soil on the heel side constitute the righting moment which counteracts the applied overturning moment. The graph of the righting moment with respect to depth of embedment shows that the rate of increase in the righting moment is greater when depth of embedment is equal to or greater than the width of footing. At this depth of embedment, the L-shaped footings have greater rate of increase in the righting moment than the square and rectangular footings. By incorporating in the design of spread footing the effect of passive pressure at the side of the column/footing, the weight of the overlying soil on the heel side of the footing at certain depth of embedment of the column/footing itself result to reduction in footing dimension. Placing footing base at a depth equal to three times the eccentricity of the applied loads reduces the overturning moment to almost zero value. In summary, depth of embedment significantly influences footing resistance to overturning.